Types of Legal Regulations of Working Time - Tatiana Mihailovna Fakhrutdinova (Сибирское юридическое обозрение, 2011)
The article deals with norms of working time. Legal standards referring to the norm of working time, which are found in labor legislation, are topical subject of research in labor law. The author examines the problem of establishing the following legal regulations of working time in the labor law: 1) work week, and 2) shift (duration of daily work), 3) an accounting period, and 4) limit of employment, and 5) working day. The author notes that while the Labour Code of the RSFSR (1922) declared that the basic legal norm of working time should be a working day (shortening of the working day was one of the main political goals of the Russian working class before 1918), the Labor Code of the Russian Federation in 2001 established the working week as the standard legal norm of working time.